2020
DOI: 10.31234/osf.io/n3fbc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human-body analogy improves mental rotation performance in people aged 86 to 97 years

Abstract: Mental rotation is a spatial ability allowing one to represent and rotate an object in one’s mind, and its performance declines with age. Given previous findings indicating that likening a to-be-rotated object to a human body improves mental rotation performance in young adults, we examined whether this human-body analogy would improve older adults’ mental rotation performance. We also tested whether the human-body analogy effect is age-dependent. In the present study, we analyzed data from 423 community-dwell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
(117 reference statements)
2
3
0
Order By: Relevance
“…In the letter MR related to visual imagery, older adults showed a stronger angle effect and longer mean ΔRTs than young adults. This replicates previous studies on declines in efficiency of visual or object-based transformations ( Cerella et al, 1981 ; Berg et al, 1982 ; Dror and Kosslyn, 1994 ; Gondo et al, 1998 ; Briggs et al, 1999 ; Band and Kok, 2000 ; De Simone et al, 2013 ; Iachini et al, 2019 ; Zhao et al, 2019 ; Muto et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the letter MR related to visual imagery, older adults showed a stronger angle effect and longer mean ΔRTs than young adults. This replicates previous studies on declines in efficiency of visual or object-based transformations ( Cerella et al, 1981 ; Berg et al, 1982 ; Dror and Kosslyn, 1994 ; Gondo et al, 1998 ; Briggs et al, 1999 ; Band and Kok, 2000 ; De Simone et al, 2013 ; Iachini et al, 2019 ; Zhao et al, 2019 ; Muto et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…The lack of difference in the angle effect aligned with Gondo et al (1998) , who reported no difference in RT slopes for the letter MR between young–old (64–74 years) and old–old (75–92 years) groups. In contrast, studies using paper-and-pencil MR tests with three-dimensional cubes reported decreased MR performance during advanced aging ( Borella et al, 2014 ; Muto et al, 2020 ). This inconsistency might arise from methodological differences in task demand, stimulus type, and/or dependent variable.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Specifically, the simple inclusion of objects with human-like features would allow us to ameliorate visuospatial assessments by considering a patient's spatial perspective-taking ability and to establish customized therapeutic approaches according to each patient's mental spatial ability. Relatedly, our recent work (Muto et al, 2020) administered a paper-and-pencil mental rotation test with almost the same objects as the present study to elderly people aged 86–97 years and revealed that performance for human-like objects was better and more preserved with age than for nonsense objects. This suggests a neural basis for the mental rotation of human-like objects that is partially different from that of the mental rotation of nonsense objects in a way that compensates for the age-related decline of the object-based mental rotation ability.…”
Section: Discussionsupporting
confidence: 65%
“…People can perform a same/different mental rotation task more efficiently when the stimuli are human bodies ( Amorim et al, 2006 ; Jansen et al., 2012 ; Voyer & Jansen, 2016 ) or cube objects with human-like features (e.g., head, face) that are analogous to human bodies ( Amorim et al, 2006 ; Krüger et al, 2014 ; Makinae et al, 2015 ; Makinae & Kasai, 2017 ; Muto et al, 2020 ; Muto & Nagai, 2020 ; Sayeki, 1981 ; Voyer & Jansen, 2016 ) compared with nonsense cube objects. Amorim et al (2006) proposed two underlying processes in the human-body advantage in mental rotation, called “spatial embodiment” and “motoric embodiment.” The spatial embodiment describes the process of projecting one's body axes onto human bodies or human-like objects with intrinsic axes (e.g., the top–bottom axis can be defined by the head position), while the motoric embodiment describes the process of the mental emulation of the posture of stimuli.…”
Section: Human-body Advantage In Mental Rotationmentioning
confidence: 99%